PENGARUH PENGETAHUAN, PERSEPSI KEGUNAAN, PERSEPSI KEMUDAHAN, PERSEPSI RISIKO TERHADAP NIAT MENGGUNAKAN QRIS - Juwita Magdalena Harianja; Dinda Indira Subagio (Bajang Institute, 2026)
The development of digital payment systems in Indonesia has shown significant growth with the introduction of the Quick Response Code Indonesian Standard (QRIS). However, the level of QRIS adoption in Batam City is still not as high as in other regions. This study aims to analyze the impact of product knowledge, perceived usefulness, perceived ease of use, and perceived risk on the intention to continue using QRIS as a digital payment method among Generation Z in Batam City. This study employs a quantitative approach using a survey method, through the distribution of questionnaires to residents of Batam City who have used QRIS. Sampling was conducted using purposive sampling, with respondents selected based on the criteria of being Generation Z and having experience using QRIS. The data obtained will be analyzed using Partial Least Squares-based Structural Equation Modeling. The research results indicate that product knowledge does not influence the intention to continue using QRIS. Perceptions of usefulness and ease of use have a positive influence on the intention to continue using QRIS, while risk perception has a negative influence. This study is expected to contribute to the development of technology acceptance theory and serve as a reference for relevant parties in promoting the continued use of QRIS in Batam, particularly among Generation Z.